2012
DOI: 10.1007/s15010-012-0362-2
|View full text |Cite
|
Sign up to set email alerts
|

Targets for antibiotic and healthcare resource stewardship in inpatient community-acquired pneumonia: a comparison of management practices with National Guideline Recommendations

Abstract: Purpose Community-acquired pneumonia (CAP) is the most common infection leading to hospitalization in the U.S. The objective of this study was to evaluate management practices for inpatient CAP in relation to IDSA/ATS guidelines to identify opportunities for antibiotic and health care resource stewardship. Methods This was a retrospective cohort study of adults hospitalized for CAP at a single institution from April 15, 2008 – May 31, 2009. Results Of 209 cases, 166 (79%) were admitted to a medical ward an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 43 publications
3
29
0
1
Order By: Relevance
“…Single‐center studies have identified that antimicrobial therapy for pneumonia is frequently prescribed for longer than recommended by guidelines, which found a similar median duration of therapy as our evaluation . Similar to Jenkins et al, we observed a high rate of fluoroquinolone prescriptions upon discharge …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Single‐center studies have identified that antimicrobial therapy for pneumonia is frequently prescribed for longer than recommended by guidelines, which found a similar median duration of therapy as our evaluation . Similar to Jenkins et al, we observed a high rate of fluoroquinolone prescriptions upon discharge …”
Section: Discussionsupporting
confidence: 87%
“…Within the Veterans Health Administration (VHA), the Antimicrobial Stewardship Taskforce (ASTF) was created to optimize care by developing, deploying, and monitoring a national‐level strategic plan for antimicrobial therapy management improvements . Although single‐center studies have found antimicrobial therapy for CAP being frequently prescribed for longer than recommended, the reproducibility of this finding across different facilities has not been assessed . The ASTF collaborated with the VHA Center for Medication Safety to assess total duration of antimicrobial therapy prescribed for veterans hospitalized with uncomplicated pneumonia…”
mentioning
confidence: 99%
“…Although stewardship efforts have largely focused on antibiotic use in the hospital [2], for patients hospitalized with common infections, the majority of the antibiotic course is completed after hospital discharge [3,4]. This suggests that optimizing prescribing at the time of discharge may be important to overall antibiotic stewardship efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Although only shown in hospital wards rather than ICU, failure to de-escalate or discontinue therapy [34,35] is also a likely contributory factor to antibiotic resistance in ICU. The exact impact of multidrug resistance (MDR) microbial organisms is difficult to quantify, depend as it does on, the causative microbe and its pathogenicity, patient populations, severity of illness and the appropriateness of therapy [36] .…”
Section: Antibiotic Resistance In Icu Its Contributors and Impactmentioning
confidence: 99%